Deriving directions through procedural task analysis. - Yuen HK; D'Amico M (Occupational Therapy in Health Care, 1998)
Task analysis is one of the essential components of activity analysis. Procedural task analysis involves breaking down an activity into a sequence of steps. Directions are the sequence of steps resulting from the task analysis (i.e., the product of the task analysis). Directions become a guide for caregivers or trainers to use in teaching clients a specific skill. However, occupational therapy students often have difficulty in writing directions that are clear enough for caregivers or trainers to carry out. Books on activity analysis only provide examples of directions without giving guidelines on how to perform the writing process. The purposes of this paper are to describe the process of procedural task analysis and to provide a guideline for writing steps of directions.